Effectiveness of Sms Advertising in Bangladesh: Drawing on Hierarchy of Effects Model - Mamun, Muhammad Ziaulhaq (Archives of Business Research, 2021)
The study explored the effectiveness of Short Message Service (SMS) advertising on customers’ purchase decision focusing awareness, knowledge, liking, preference, conviction, and purchase attributes of Hierarchy of Effects Model. A total of 180 mobile phone subscribers were surveyed adopting non-probability convenience and judgmental sampling techniques through a structured questionnaire. It is found that none of the attributes have positive impact on the subscribers’ behavior. Purchase is found to be the most ineffective attribute followed by Conviction and Liking. Awareness, Knowledge, and Preference are least ineffective ones. However, SMS ad which explicitly mentions the company name and offers in the title, somewhat gets subscribers’ attention. It is noted that the SMS ads do not provide enough information, accessibility, and convenience. Brand loyalty and brand image of the products advertised have weak positive impact on consumer preference. The respondents view SMS ads mostly unconvincing and ineffective; but call rate packages, internet purchases and product discount purchases fared not so poorly. However, there are situations where SMS can be utilized effectively. As SMS advertising do not really incur much additional cost for the telecom companies, it can provide an avenue for information dissemination, as well as, to generate revenue from offers they promote.